Pengaruh Pemberian Stimulan pada Tanaman Karet (Hevea brasiliensis) - Pradana, Aryanda; Tamba, Sihol Suganda; Winawung, Debby Setya; Amelia, Lisa; Marselly, Ravela; Febriyanti, Dea; Putri, Anggita (Seminar Nasional Lahan Suboptimal, 2022)
Pradana A, Tamba SS, Winawung DS, Amelia S, Marselly R, Febriyanti D, Putri A. 2022. The influence of application stimulant of rubber (Hevea brasiliensis) In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 309-317. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Stimulants are stimulants for rubber plants, giving stimulants aims to increase latex production in rubber plants. This survey aimed to determine the effectiveness of giving stimulants to rubber plants (Hevea brasiliensis). The type of stimulant used is 30 ml of Ethrel and 60 ml of water then mix into a bowl, then stir until evenly distributed. Then apply the stimulant liquid to the tapping stream, smearing is done in the same direction, from top to bottom. The results of this survey indicate that giving stimulants can increase latex productivity in rubber plants. Rubber trees that have been given stimulants can produce more latex than rubber trees that are not given stimulants. A rubber tree given a stimulant will produce a full bowl of latex in less than a day. Meanwhile, rubber trees that are not given stimulants need 2-3 days to get one cup of latex. So the conclusion of this survey proves that the use of stimulants on rubber plants is much more effective than rubber that is not given stimulants. The use of stimulants must pay attention to the right dose, because excessive use of stimulants or not in accordance with the dose will cause diseases in rubber plants such as dry tapping grooves.